Learning Together: Implementation of a Peer-Tutoring Intervention Targeting Academic and Social–Emotional Needs. Issue 3 (10th May 2018) - Capp, Gordon; Benbenishty, Rami; Astor, Ron Avi; Pineda, Diana
Abstract: Schools continue their efforts to concurrently support the academic and social–emotional needs of students. Peer-tutoring programs are frequently used to effect positive change for students in a variety of academic and social–emotional domains. In addition, these programs are often used to target specific students or needs on a school campus. School social workers are uniquely suited to consider, implement, and evaluate programs targeting multiple student outcomes. This article presents a case example of a Learning Together, Math Together program implemented in a K–8 school in a small school district in Southern California. Quantitative data were gathered at three times during one school year. Semistructured interviews were conducted with teachers and class coordinators during the school year, and observations from members of the research team were gathered. Participants included 60 tutors, 45 tutees, three class coordinators, and two program coordinators. Tutors were sixth, seventh, and eighth-grade students; tutees were fourth-, fifth-, and sixth-grade students. Results indicate that the program met student expectations, and parents were also satisfied. Teacher reports indicated small academic improvements, but many indicated larger social–emotional improvements. Teacher feedback was also used to create suggestions for improving subsequent implementation of Learning Together.